REALIZATION OF THE PHENOTYPIC EFFECT OF CHROMOSOMAL ABERRATIONS IN HUMANS - K. N. Grinberg; V. I. Kukharenko (Вавиловский журнал генетики и селекции)
Factors determining the phenotype formation in patients with abnormal karyotype (including those with Down’s syndrome) have been discussed for several decades. Earlier, we considered factors affecting phenotype formation in patients with chromosomal aberrations (Grinberg, 1978, 1982; Grinberg, Kukharenko, 1992). We believe that the general concept of the phenotypic manifestation of chromosomal disbalance must take into account the following factors:1. The alteration in the number of chromosomes, in addition to specific effects connected with the dose of the genes located in a particular chromosome is accompanied by a nonspecific effect, which is manifested in the oppression of growth and development of the organism.2. Birth defects observed in persons with chromosomal aberrations are persisting conditions, which are normal at earlier developmental stages. The main effects of chromosomal aberrations are hypomorphic. Nevertheless, these birth defects actually do not differ from developmental defects caused by particular genes and teratogenic environmental factors.3. The phenotypic manifestation of chromosomal imbalance may be based on disturbances of the basic and elementary events in morphogenesis, occurring at the cell level. Such events are proliferation and migration of cells, specific reception, and induction relationships.4. It is supposed that changes of metabolic homeostasis in cells with abnormal karyotypes favor the manifestation of the latent variability of structures that support the basic morphogenetic functions in cells. It is conceivable that chromosomal aberrations strengthen the evolutionarily conditioned variability towards the delay of maturation of cellular and tissue structures, which is the key link in the pathogenesis associated with chromosomal imbalance.